Pemberdayaan KWT Mekar Sari Kelurahan Kefa Selatan melalui Pelatihan Pembuatan Kompos Biochar untuk Budidaya Tanaman Hortikultura - Deseriana Bria; Natalia Desy Djata Ndua; Hyldegardis Naisali; Jefrianus Nino; Wilda Lumban Tobing; Faustinus Kadha; Bernardinus Kolo (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The issue of declining soil fertility and limited access to sustainable agricultural inputs is a major challenge for smallholder farmers in Kefa Selatan, Timor Tengah Utara Regency, East Nusa Tenggara Province. In response, a community service program was initiated under the title Empowerment of KWT Mekar Sari in Kefa Selatan Subdistrict through Biochar Compost Training for Horticultural Cultivation. The objective of this activity was to enhance the capacity of local farmers, particularly members of the Mekar Sari Women Farmers Group (KWT), in producing and utilizing biochar compost to improve soil quality and increase horticultural crop productivity. The activity was carried out from July to September 2024 in Kefa Selatan and involved 15 local farmers as participants, facilitated by a team of 7 lecturers and students from the University of Timor. The methods employed included educational sessions on the benefits of compost, hands-on training in biochar compost production, and demonstration of its application in horticultural crop cultivation. As a result, participants gained practical knowledge and skills in sustainable composting techniques and showed increased awareness of organic farming benefits. The training also stimulated greater community engagement and environmental awareness. This program is expected to serve as a model for similar initiatives in other rural communities.